The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2011
DOI: 10.4049/jimmunol.1002620
|View full text |Cite
|
Sign up to set email alerts
|

Stat6 and c-Jun Mediate Th2 Cell-Specific IL-24 Gene Expression

Abstract: TCR signaling regulates multiple aspects of T cell function by controlling expression of various cytokine genes. IL-24 is a multifunctional cytokine belonging to the IL-10 family. It displays anticancer effects in diverse cancer cells and regulates immunopathology of psoriasis and rheumatoid arthritis. IL-24 also plays an important role in B cell differentiation. Mouse IL-24 gene is selectively expressed in activated Th2 cells upon TCR stimulation. However, the molecular mechanisms by which TCR stimulation ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 55 publications
1
32
0
Order By: Relevance
“…A recent report indicated that IL-24 expression is Th2 specific, mediated in part by STAT6 function through the IL-24 promoter [67]. We asked whether there might be functional elements dispersed throughout this locus, as found for the IL4/IL13/IL5 locus; these can be identified through genomic analysis, especially when multiple datasets are combined [4,68].…”
Section: Resultsmentioning
confidence: 99%
“…A recent report indicated that IL-24 expression is Th2 specific, mediated in part by STAT6 function through the IL-24 promoter [67]. We asked whether there might be functional elements dispersed throughout this locus, as found for the IL4/IL13/IL5 locus; these can be identified through genomic analysis, especially when multiple datasets are combined [4,68].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the proximal promoter of IL24 contains binding sites for STAT6 and JUN, and these transcription factors are thought to function synergistically to regulate IL-24 production by T H 2 cells 63 . Production of IL-24 by group 2 ILCs has not yet been reported.…”
Section: T Cells and Innate Lymphoid Cells T Cells Are A Primary Celmentioning
confidence: 99%
“…ϩ T cells were cultured in vitro under Th1, Th2, and Th9 differentiation conditions by following the previously reported studies (6,51). Expression level of IL-9 was measured among the various in vitro differentiated T helper subsets.…”
Section: Identification Of Transcription Factor Binding Sites In Il-9mentioning
confidence: 99%
“…In general, enrichment of acetyl histone H3 (AcH3), acetyl histone H4 (AcH4) and histone H3 lysine 4 dimethylation (H3K4Me2) to promoters correlates well with their transcriptionally active status (30,50,51). Thus, to further confirm the differential chromatin structure of the IL-9 promoter between WT and NFAT1 Ϫ/Ϫ Th9 cells, relative amounts of recruited AcH3, AcH4, and H3K4Me2 levels were analyzed by a ChIP assay.…”
Section: Reduced Chromatin Accessibility Of Il-9 Promoter In Nfat1mentioning
confidence: 99%